Pro-poor Curves and Pro-Poor Growth Index: Case Study in South Kalimantan Province - Murjani, Ahmadi (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2021)
This paper aims to analyze the nature of the growth in the South Kalimantan province of Indonesia. Different definitions of pro-poor growth, as well as the methods for pro-poor growth classification, have encouraged this paper to use the partial (Growth Incidence Curve and Pro-Poor Growth Curve) and full approaches (Pro-Poor Growth Index). After examining the data spanning from 2010 to 2020, this paper arrives at conclusions. In general, the growth in South Kalimantan is pro-poor but in the period from 2010 to 2016 most benefits of the growth are absorbed by the richer people. In contrast, the growth is pro-poor from the period from 2016 to 2020 and the benefits of the growth are received more by poor people. Also, this paper underlines the importance of detailed examinations for all approaches to avoid a mixed result within the period of examination.